ANALISIS PENYEBAB STRES KERJA PADA PETUGAS CLEANING SERVICE MENGGUNAKAN KUESIONER PERMENAKER NO. 5 TAHUN 2018 - Amanda Puspa Putri; Adistia Puji Pramesti; Ahsinatul Afifah; Denny Oktavina Radianto (JOURNAL SAINS STUDENT RESEARCH, 2024)
Work stress is still a problem that is often complained about by workers in various industries. Work stress can adversely affect employee performance and health. This study aims to analyze the causes of work stress by using the PERMENAKER No. 5 2018 questionnaire to 20 respondents. The research method used is a quantitative cross sectional study with validity and reliability tests. The validity test results show that all questionnaire items have a rcount value higher than the rtable. The qualitative load variable has the highest value (6.250), while role confusion variable has the lowest value (3.663). The reliability test results showed good results with an rcount value of 0.85144. The univariate test results show that the stressors associated with job stress are role confusion, role conflict, quantitative burden, qualitative burden, career development, and responsibility for others. The majority of respondents experienced moderate stress (60%), followed by severe stress (35%) and mild stress (5%). The main factor that became the stressor of this condition was role conflict with the largest distribution of 17 people (85%). Based on these results, agencies need to pay more attention to factors that affect job stress and implement programs such as socialization to reduce its impact.